New luxury management : creating and managing sustainable value across the organization - Rigaud-Lacresse, Emmanuelle; Pini, Fabrizio Maria (Palgrave Macmillan, 2017)
Presenting a vision of the luxury sector and its management, this edited book describes "the new luxury" through a comprehensive view of the value chain, from concept to market. The authors argue that the main characteristics of "luxury" are linked to specific resources and competencies found throughout the value chain and that value is a result of the interaction between the brand and stakeholders, and more precisely with their clients. Taking an interdisciplinary approach, New Luxury Management encompasses both strategic and functional aspects of luxury management, providing innovative solutions to the successful creation and management of value across the organization, from leadership, human resources, financial management, marketing and economic perspectives.
Keywords: Luxury goods industry.; Luxuries.; elektronické knihy; electronic books